Detecting coastline changes use GIS geospatial techniques in Island Carey- Morib Coast, Selangor, Malaysia - Nor Lita Fadilah Rameli,; Mokhtar Jaafar, (Institute of the Malay World and Civilization, Universiti Kebangsaan Malaysia, 2018)
Coastal area is one of the very dynamic landscapes where erosion and deposition processes always occur. Therefore, a study is been conducted to detect changes of coastline caused by both processes at Carey Island-Morib coast. Geospatial technology that involved the use of GIS and satellite imagery had been apply in this study. Data sources are topography map of 1974 and SPOT image of 2008. The results show that coastal erosion process was dominant in Carey Island, while deposition process was the case for Morib coast. The average value of eroded distance is higher than the average value of deposited distance, which is 170 and 157 m, respectively. Coastal erosion process in Carey Island could be relate to the movement of big ships along Malacca Strait and Port Klang that is capable of producing big waves and eroding energy. Meanwhile deposition process in Morib coast could be relate to the transfer of land sediment to the estuary and along the coast by low-energy wave. These findings should be support with fieldwork study that could verify the effectiveness of coastal geomorphologic agents and the impact of human activities on land in influencing the changes of coastline in Carey Island-Morib coasts.